2017
DOI: 10.1177/0963689717714092
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Mild Traumatic Brain Injury

Abstract: Mild traumatic brain injury (mTBI) represents a significant public healthcare concern, accounting for the majority of all head injuries. While symptoms are generally transient, some patients go on to experience long-term cognitive impairments and additional mild impacts can result in exacerbated and persisting negative outcomes. To date, studies using a range of experimental models have reported chronic behavioral deficits in the presence of axonal injury and inflammation following repeated mTBI; assessments o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(93 citation statements)
references
References 275 publications
(410 reference statements)
3
75
1
1
Order By: Relevance
“…In terms of the pathophysiological outcomes resulting from multiple mTBIs, research using various experimental models has demonstrated diffuse axonal injury and demyelination (Bailes, Dashnaw, Petraglia, & Turner, 2014; Fehily & Fitzgerald, 2017), as well as cumulative damage to hippocampal cells (Slemmer, Matser, De Zeeuw, & Weber, 2002). Given that myelin plays a key role in information processing speed and that hippocampal functioning is essential for memory performance, it is not surprising that observed pathophysiological changes in white matter and the hippocampus have been linked to motor and memory dysfunction following multiple mTBIs in both animal and human studies (Mouzon et al, 2012; Multani et al, 2016; Niogi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the pathophysiological outcomes resulting from multiple mTBIs, research using various experimental models has demonstrated diffuse axonal injury and demyelination (Bailes, Dashnaw, Petraglia, & Turner, 2014; Fehily & Fitzgerald, 2017), as well as cumulative damage to hippocampal cells (Slemmer, Matser, De Zeeuw, & Weber, 2002). Given that myelin plays a key role in information processing speed and that hippocampal functioning is essential for memory performance, it is not surprising that observed pathophysiological changes in white matter and the hippocampus have been linked to motor and memory dysfunction following multiple mTBIs in both animal and human studies (Mouzon et al, 2012; Multani et al, 2016; Niogi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Guskiewicz and colleagues [12] showed that collegiate football players with a history of concussion are 3.4 times more likely to sustain a second concussion within the same season. This potential for a second impact is important because several studies have shown that sustaining an additional injury when the brain is particularly susceptible can significantly exacerbate physiological damage and functional deficits [4,10,[15][16][17]. Giza and DiFiori [4] reported that if the brain is injured during this "window", there exists a cumulative effect of injurious processes and worsened neurological outcomes; however, when there is a greater interval between the mTBIs, cumulative deficits are not observed [18].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, dysregulation of neuronal excitability and extracellular potassium operate on short time-scales and are responsive to injury severity, which are compatible with our observed synergistic effects for injuries at short inter-injury intervals and for moderate, but not severe TBI. Downstream consequences of misregulated neurotransmission and extracellular potassium are varied, but may include changes in oxidative stress and inflammation (Guerriero et al 2015; Fehily and Fitzgerald 2017; Khatri et al 2018).…”
Section: Discussionmentioning
confidence: 99%